Assessment of biomedical waste management of a multispeciality hospital in the light of new BMW rules 2016: what has changed from the past? - Hiremath, Ravishekar N.; Basandra, Sumeena; Kunte, Renuka; Ghodke, Sandhya; Edwards, Tarana Sarah; Yadav, Jyoti; Yadav, Arun K.; Patil, Shailaja (International Journal Of Community Medicine And Public Health, 2017)
Background: The hierarchies of Bio-Medical Waste (BMW) is largely based on the concept of the “3Rs”, namely reduces, reuse and recycle, and broadly relates to the sustainable practice of resources. The objectives of the study were to assess the Bio-Medical Waste (BMW) Management operating system in a multispecialty hospital and discuss the situation in terms of newly introduced BMW Rules 2016. Methods: A hospital based cross-sectional study was carried out by collecting data by means of independent surveys involving on-ground operating system of BMW management across different wards, outpatient departments, emergency departments, intensive care units and laboratories in the hospital. Results: The hospital was following Bio Medical Waste (Management and Handling) Draft rules, 2011 in the management of BMW. All the wastes were categorized into 8 categories as per 2011 draft rules. Efficient waste segregation, collection, storage, transport and waste treatment were followed as per norms with regular training of all health care workers under the close supervision and monitoring by dedicated BMW management committee. The hospital was registered for BMW management and renewal was being carried out every three years. Conclusions: It can be concluded that the hospital had an efficient and a well-organized BMW management system in place that was even conforming to the latest BMW Management Rules 2016 to some extent. Moreover, the hospital could upgrade the techniques of BMW management as per the newly introduced latest guidelines. As far as the categorization of BMW is concerned, it has to be changed accordingly to the new rules. Needless to say, a regular training and monitoring of BMW Management at all hospitals is the need of the hour and has a long way to go for environmental and human health.